Breakthrough Exophiala dermatitidis infection during prophylactic administration of micafungin during second umbilical cord blood transplantation after graft failure. Issue 2 (12th February 2018) - Watanabe, Naoki; Gotoh, Akihiko; Shirane, Shuichi; Hamano, Yasuharu; Hirai, Yuji; Shimizu, Maika; Nakamura, Ayako; Matsumoto, Kana; Morita, Kunihiko; Mori, Takeshi; Ohsaka, Akimichi; Komatsu, Norio
Abstract: Exophiala dermatitidis infections in patients with hematological malignancies are very rare. Our patient had a blood stream infection caused by E. dermatitidis following the second umbilical cord blood transplantation (UCBT) after graft failure during the first UCBT. To our knowledge, this is the first report describing a breakthrough fungal infection caused by E. dermatitidis during the prophylactic administration of micafungin (MCFG). Therefore, MCFG‐treated patients should be monitored for breakthrough E. dermatitidis infection during hematopoietic stem cell transplantation.